Pedir, prometer e pagar: escritos, imagens e objetos dos romeiros de Canindé. - Silva, Lucília Maria Oliveira (2007)
This research discusses the religious practices of São Francisco pilgrims from Canindé (CE), Brazil, apprehending their relationships with the sacred according to their written prayers, and its purpose. This aim arose mainly from the analysis of devotees’ letters and photographs sent to Canindé to thank, ask for, or tell miracles. According to these choices and the availability of the sources, I opted to not delimit an inflexible period in order to consider certain inherent questions. Thus, at first I tried to understand how Canindé became a holy place by the narratives of miracles, the Church action and the devotees’ interpretations. Besides that, I focused on some peculiarities relating devotees’ concepts about the saints and the tactics for miracles attainment. Therefore, I talked about the miracles, that is, the needs presented by the pilgrims. This allowed us to perceive how they think and live deeply their daily historical experiences relating them with a concept of faith and protection.